Tathawwur Taallum Al-Lughah Al-Arabiyah AL-Qaim ‘ala Asasi Al-Tiknulujiya - Ahsanuddin, Mohammad; Rozi, Fakhrur; Mahendra, Romi (Cordova Journal language and culture studies, 2023)
Language teaching is part of education in general, but language teaching has different characteristics and purposes from education in its overall concept. Language teaching does not mean teaching about the language, but it tends to teach the methods and techniques for pronouncing the language. Technology is a Greek word meaning a craft, workmanship, or art, and it is a suffix meaning science. Technology is work that is concerned with improving performance and formulation during scientific application. Based on this, it can be concluded that education technology does not require the presence of technology in it, and education based on technology requires the presence of technology during the lesson. The history of the emergence of technology-based education, especially language education, corresponds to the emergence of the technologies themselves on the ground.